INTEGRATED REPORTING CONTENT ELEMENTS AND MARKET PRICE OF LISTED BANKS IN NIGERIA (Journal of Global Accounting, 2024)
This study investigated the effect of integrated reporting (IR) content elements on the market price per share (MKPF) of listed banks in Nigeria. Specifically, it examines the impact of three key IR disclosures: organizational overview and external environment (OEE), business model disclosures (BMD), and risks and opportunities (RO). Using Ordinary Least Squares (OLS) regression the research analyzed data from 5 listed banks in the Nigerian Exchange Group (NGX) from 2013 to 2022 to explore the relationship between these reporting elements and market performance. The findings indicate that OEE has a significant positive effect on MKPF, while BMD and RO show no statistically significant influence. These results highlight the importance of transparency in organizational and environmental disclosures to foster investor confidence. The study concluded with recommendations for banks to enhance their integrated reporting practices and for regulators to introduce policies that promote comprehensive disclosures.
Keywords: Business Model; Integrated Reporting; Market Price Per Share; Nigerian Banks; Organizational Overview, Risks and Opportunities